2007
DOI: 10.1152/ajpheart.01283.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species-mediated signaling in endothelial cells

Abstract: Zhang DX, Gutterman DD. Mitochondrial reactive oxygen species-mediated signaling in endothelial cells. Am J Physiol Heart Circ Physiol 292: H2023-H2031, 2007. First published January 19, 2007; doi:10.1152/ajpheart.01283.2006.-Once thought of as toxic by-products of cellular metabolism, reactive oxygen species (ROS) have been implicated in a large variety of cell-signaling processes. Several enzymatic systems contribute to ROS production in vascular endothelial cells, including NA(D)PH oxidase, xanthine oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
281
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(294 citation statements)
references
References 93 publications
8
281
0
5
Order By: Relevance
“…The lack of similar effect induced by L-glucose indicated that glucose entry and metabolism into cells was required for increased ROS formation. Increased ROS formation was linked to mitochondrial dysfunction, consistent with previous reports (10), in which complexes I and III were involved-the former probably by reverse electron flow from complex II (46). Incubation of HMEC-1 cells with the mitochondrial inhibitors for 24 h produced significant cytotoxicity and masked the role of complex I in hyperglycemia-induced ROS formation.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of similar effect induced by L-glucose indicated that glucose entry and metabolism into cells was required for increased ROS formation. Increased ROS formation was linked to mitochondrial dysfunction, consistent with previous reports (10), in which complexes I and III were involved-the former probably by reverse electron flow from complex II (46). Incubation of HMEC-1 cells with the mitochondrial inhibitors for 24 h produced significant cytotoxicity and masked the role of complex I in hyperglycemia-induced ROS formation.…”
Section: Discussionsupporting
confidence: 89%
“…The transfer of electrons from complex I to V generates a proton concentration gradient across the inner mitochondrial membrane, sustaining the MMP and driving ATP synthesis (34). A failure of efficient electron transport and ATP synthesis induced by oxidative stress results in the accumulation of free radicals and leads to mitochondrial dysfunction (35). In the present study, pre-treatment with pinacidil was found to increase ATP synthesis.…”
Section: Discussionsupporting
confidence: 47%
“…In addition to CYP1, several sources of ROS exist, notably the mitochondrial electron transport chain, nicotinamide adenine dinucleotide phosphate-oxidase, and cyclooxygenases. [39][40][41] Note that IAA also has a prooxidant effect in renal tubular cells. 42 Via prooxidant, proinflammatory, and prothrombotic 9 mechanisms, IAA could act as a mediator of endotheliotoxicity of uremia.…”
Section: Discussionmentioning
confidence: 99%